White House down - Emmerich, Roland; Tatum, Channing; Foxx, Jamie; Gyllenhall, Maggie, 1977-; Wander, Thomas; Kloser, Harald, 1956- (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
While John Cale, a Capitol Policeman, is taking his daughter on a tour of the White House it is taken over by a paramilitary group, and it is up to John to save the president and his country.
Originally released as a motion picture in 2013.
Dolby digital 5.1, wide screen 2.40:1.
Features: Dynamic duo, Men of action, Roland Emmerich : upping the ante, Meet the insiders.
Camera, Anna J. Foerster ; editor, Adam Wolfe ; music, Thomas Wander, Harald Kloser.
Channing Tatum, Jamie Foxx, Maggie Gyllenhaal, Jason Clarke, Richard Jenkins, Joey King, James Woods, Nicolas Wright, Jimmi Simpson.
MPAA rating: PG-13.
Keywords: White House (Washington, D.C.) -- Drama; Secret service -- Drama; Terrorists -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Feature films